The first record of the mole crab (Albunea carabus L. 1758, Decapoda, Anomura, Hippidea) in the Gulf of Antalya - Gökoğlu, Mehmet; Teker, Serkan; Gökoğlu, Kemal (Universitas Malikussaleh, 2019)
The first occurence of the mole crab (Albunea carabus L. 1758) in the Gulf of Antalya. During a commercial shrimp fishery oparation in May, 2016, A different type of crab was caught in the Gulf of Antalya, Bogazkent (KöprüÃ§ayÄ±). This unknown sample was brought to Akdeniz Ãœniversity Fisheries Laboratory and It was stored. Sample was caught with shrimp nets that were left at depths of 10-20 m in the Gulf of Antalya, Bogazkent (KöprüÃ§ay River). It has been determined that this elongated mole, caught in the identification of the species, is Albunea carabus L. 1758, known as the dengue. Mole crab (Albunea carabus L. 1758) was reported for the first time from the Gulf of Antalya via this article.Keywords: Albunea carabus; the Gulf of Antalya; mole crab